RESPONSE OF STUDENTS OF EDUCATION FACULTY OF SOCIAL AND POLITICAL SCIENCES STATE UNIVERSITY OF SURABAYA REGARDING THE FIRST DEBATE OF THE 2024 PRESIDENTIAL ELECTION - Diana, Nana; Mustika Kartika Sari, Maya (Kajian Moral dan Kewarganegaraan, 2025)
The 2024 presidential election is different from previous general elections, which gave rise to various responses from the public, especially education students at the Faculty of Social and Political Sciences, Surabaya State University. This research uses a qualitative method with a phenomenological design. The informants for this research were education students from the Faculty of Social and Political Sciences, Surabaya State University, consisting of S1 Geography Education, S1 Social Sciences Education, S1 Pancasila and Citizenship Education and S1 History Education. The focus of this research is the responses given by research informants regarding the first debate in the 2024 presidential election. The data collection techniques used were interviews and documentation. The data analysis technique in this research uses the Miles Huberman analysis model. The results of this research show that education students at the Faculty of Social and Political Sciences, Surabaya State University, responded to the first debate in the 2024 presidential election by giving their opinions both in person and virtually. There are several ways for education students to respond to the first debate in the 2024 presidential election, namely by openly discussing discussions and discussing discussions via WhatsApp groups. Several students responded to the debate in open discussions with family and friends. And discussions were held via the WhatApps group with family and friends regarding the issues of the first debate for the 2024 presidential election that were being discussed.